ORIGINS OF COMETS: THE HYPOTHESIS OF RELICT RESERVOIR OF COMETARY BODIES (CB) AS UNITARY STORE OF COMETS OF THE SOLAR SYSTEM - Tsitsin, F. A.; Chepurova, V. M.; Genkin, I. L. (Одеські астрономічні публікації, 2017)
Solar system comets come from a relict reservoir of cometary bodies (CB). The reservoir consists of two components of common origin, but highly different spatial, dynamical and kinematical characteristics: 1. Dynamically stable on cosmogonic time-scale component formed by Kazimirchak-Polonskaya (K.-P.) belts laying between giant planets (GP) and beyond Neptune (including the Kuiper Belt). The component extends up to the unknown boundaries of the zone of primordial planetesimals formation and (thanks to CB collisions pushing the CB away from the zone of stability) provides us with periodic comets (with the exception of almost all the parabolic ones).2. Swarm of dissipantes moving on Brown-type trajectories; at present the swarm may be of a size of no more than 100 ps, but expand diffusing "into the Galaxy", and provide, thanks to statistically inevitable returns of part of the CB to the Sun, "quasiparabolic" comets, including: a) elliptic quasiparabolic; b) non- distinguishable from parabolic; c) slightly hyperbolic comets. The CB that populate the nearest belt (the one between the orbits of Jupiter and Saturn) must beas bright as 23 - 24th magnitude and consequently, in principle, observable.